Complementary insights into gut viral genomes: a comparative benchmark of short- and long-read metagenomes using diverse assemblers and binners - Huarui Wang; Chuqing Sun; Yun Li; Jingchao Chen; Xing-Ming Zhao; Wei-Hua Chen (Microbiome)
Abstract Background Metagenome-assembled viral genomes have significantly advanced the discovery and characterization of the human gut virome. However, we lack a comparative assessment of assembly tools on the efficacy of viral genome identification, particularly across next-generation sequencing (NGS) and third-generation sequencing (TGS) data. Results We evaluated the efficiency of NGS, TGS, and hybrid assemblers for viral genome discovery using 95 viral-like particle (VLP)-enriched fecal samples sequenced on both Illumina and PacBio platforms. MEGAHIT, metaFlye, and hybridSPAdes emerged as the optimal choices for NGS, TGS, and hybrid datasets, respectively. Notably, these assemblers recovered distinct viral genomes, demonstrating a remarkable degree of complementarity. By combining individual assembler results, we expanded the total number of nonredundant high-quality viral genomes by 4.83 ~ 21.7-fold compared to individual assemblers. Among them, viral genomes from NGS and TGS data have the least overlap, indicating the impact of data type on viral genome recovery. We also evaluated four binning methods, finding that CONCOCT incorporated more unrelated contigs into the same bins, while MetaBAT2, AVAMB, and vRhyme balanced inclusiveness and taxonomic consistency within bins. Conclusions Our findings highlight the challenges in metagenome-driven viral discovery, underscoring tool limitations. We advocate for combined use of multiple assemblers and sequencing technologies when feasible and highlight the urgent need for specialized tools tailored to gut virome assembly. This study contributes essential insights for advancing viral genome research in the context of gut metagenomics. Video Abstract